Effect of N, N-dimethylglycine (DMG) supplementation on haematological parameters and frequency of CD4+ and CD8+ T cells in cats post-vaccination - Shahril Agus, Syahir Aiman; Shamsul-Bahri, Nurul Afiqah; Juliana Syafinaz, .; Mohd Sadali, Muhammad Farris; Hazilawati Hamzah, .; Mustaffa-Kamal, Farina (Universiti Putra Malaysia, 2025)
N, N-Dimethylglycine (DMG) is a commonly used nutraceutical in veterinary medicine, which is claimed to have immunomodulating properties. This novel study investigated the effect of DMG supplementation on feline haematological parameters and the percentages of CD4+ and CD8+ T cells after vaccination with a single-dose commercial core vaccine. A total of twelve neutered cats were divided into control (n=6) and treatment groups (n=6) and received one dose of feline core vaccine at day 0. The treatment group then received oral DMG supplementation (125 mg/mL) twice daily for 14 days. Blood samples were collected on days 0 and 15 for haematological, differential cell count, and T cell phenotyping analysis. Haematological analysis revealed no significant difference between the control and treatment groups after 14 days of the experiment. At post-treatment, the neutrophil percentage of the treatment group was significantly lower (p=0.0238) compared to the control group, while the lymphocyte percentage of the treatment group was significantly higher (p=0.013) compared to the control group. The reduction in neutrophil percentage could be due to bromelain, an anti-inflammatory enzyme, while an increase in lymphocyte percentage could be attributed to an increase in B cell or NK cell subsets instead of T cells. Future research is warranted to investigate the effects of DMG on B cells and natural killer cell activation and to explore the long-term effects of DMG supplementation on feline immune health.